2018
DOI: 10.3390/genes10010019
|View full text |Cite
|
Sign up to set email alerts
|

Roles of Elongator Dependent tRNA Modification Pathways in Neurodegeneration and Cancer

Abstract: Transfer RNA (tRNA) is subject to a multitude of posttranscriptional modifications which can profoundly impact its functionality as the essential adaptor molecule in messenger RNA (mRNA) translation. Therefore, dynamic regulation of tRNA modification in response to environmental changes can tune the efficiency of gene expression in concert with the emerging epitranscriptomic mRNA regulators. Several of the tRNA modifications are required to prevent human diseases and are particularly important for proper devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 219 publications
(312 reference statements)
1
49
0
Order By: Relevance
“…The ASL modifications (c)t 6 A and mcm 5 (s 2 )U, found in yeast tRNAs respectively at positions 37 and 34, are critical for correct pre-structuring of the ASL [13][14][15][16][17]. Severe diseases in humans [18][19][20][21][22] and very similar phenotypes in yeast S. cerevisiae [3,29,37] are observed as a result of deficiencies in both these modifications. The sua5 elp3 mutant (lacking both t 6 A and mcm 5 U modifications), is viable in the YPD medium but cannot grow in the presence of various exogenous stressors such as elevated temperature, diamide or alternative carbon sources.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ASL modifications (c)t 6 A and mcm 5 (s 2 )U, found in yeast tRNAs respectively at positions 37 and 34, are critical for correct pre-structuring of the ASL [13][14][15][16][17]. Severe diseases in humans [18][19][20][21][22] and very similar phenotypes in yeast S. cerevisiae [3,29,37] are observed as a result of deficiencies in both these modifications. The sua5 elp3 mutant (lacking both t 6 A and mcm 5 U modifications), is viable in the YPD medium but cannot grow in the presence of various exogenous stressors such as elevated temperature, diamide or alternative carbon sources.…”
Section: Discussionmentioning
confidence: 99%
“…Early structural studies showed that t 6 A is crucial for the prevention of U33-A37 pairing, thus stabilizing the anticodon open-loop configuration, and that both modifications are critical for correct pre-structuring of the ASL [13][14][15][16][17]. Deficiencies in both these modifications lead to severe neurological diseases [18][19][20][21][22], and the yeast Saccharomyces cerevisiae has been a long-standing model to study their synthesis and function [23][24][25][26][27][28]. In yeast, t 6 A is found at position 37 of tRNAs that decode ANN codons and is further modified to ct 6 A in several tRNAs such as tRNA Lys UUU [29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Notably, defects in tRNA modification have emerged as the cause of diverse neurological and neurodevelopmental disorders, thereby highlighting the critical role of tRNA modification in human health and physiology (Angelova et al, 2018; Ramos & Fu, 2019). In particular, the brain appears to be sensitive to any perturbation in translation efficiency and fidelity brought about by defects in tRNA modifications, as evidenced from the numerous cognitive disorders linked to tRNA modification enzymes such as: the Elongator complex (Hawer et al, 2018; Kojic & Wainwright, 2016); ADAT3 (Alazami et al, 2013; El‐Hattab et al, 2016; Ramos, Han, et al, 2019); NSUN2 (Abbasi‐Moheb et al, 2012; Khan et al, 2012; Martinez et al, 2012); FTSJ1 (Dai et al, 2008; Freude et al, 2004; Froyen et al, 2007; Gong et al, 2008; Guy et al, 2015; Ramser et al, 2004; Takano et al, 2008); WDR4 (Chen et al, 2018; Shaheen et al, 2015; Trimouille et al, 2018); KEOPS complex (Braun et al, 2017); PUS3 (Abdelrahman, Al‐Shamsi, Ali, & Al‐Gazali, 2018; Shaheen, Han, et al, 2016); CTU2 (Shaheen, Al‐Salam, El‐Hattab, & Alkuraya, 2016; Shaheen, Mark, et al, 2019); TRMT10A (Gillis et al, 2014; Igoillo‐Esteve et al, 2013; Narayanan et al, 2015; Yew, McCreight, Colclough, Ellard, & Pearson, 2016; Zung et al, 2015); PUS7 (de Brouwer et al, 2018; Shaheen, Tasak, et al, 2019); and ALKBH8 (Monies, Vagbo, Al‐Owain, Alhomaidi, & Alkuraya, 2019).…”
mentioning
confidence: 99%
“…MLX and YBX-1 are known glycolytic shift regulators—controlling retrograde mitochondrial signaling to the nucleus, expression of glycolytic and lipogenic genes, and integrating PI3K/AKT signaling to glycolysis (Amal et al, 2015; Billin and Ayer, 2006; Butow and Avadhani, 2004; Diolaiti et al, 2015; Lasham et al, 2013; Sans et al, 2006; Stoltzman et al, 2008; Suresh et al, 2018; Xu et al, 2017). MED27, MRPL12 and ELP5 further contribute to these activities (Alexander et al, 2013; Catarina et al, 2014; Close et al, 2012; Fisher, 2018; Frei et al, 2005; Hawer et al, 2018; Rapino and Close, 2018). The transition to a more proliferative phenotype is highlighted by the activation of BUD31, YBX-1, SARNP, TARBP2, SIVA1 , and PHB.…”
Section: Resultsmentioning
confidence: 99%